The Fox in the Field : A WWII Novel of India - Allington, Maynard (Washington Brassey's (US) A Maxwell Macmillan Company, 1994)
The world is at war, and India is ripe for subversion and revolution. Four people stand at history's crossroads: . Subhas Bose - a fanatical Indian nationalist whose army of ex-POWs stands poised to invade India from the east to help the Japanese cut Allied supply routes from India into China. Bose's goal is an Indian uprising against the British. Derek Carr - a card counter and professional cheat, more comfortable at a baccarat table than the game of espionage. A familiar figure in the grand casinos of Europe before World War II, he suddenly turns up in Bombay. Rutger Kordt - a young German scholar who spent six years in India before the war studying ancient ruins and the mystical practice of holy ascetics. Now a ruthless officer in German intelligence, he lands by U-boat on the Indian coast with a mission that will have devastating effects. Ashley Vora - a stunningly beautiful Anglo-Indian whose own heritage compels her to choose between two conflicting worlds. Married to a wealthy Parsi businessman; she has become a militant activist for Indian independence from the British. Their link is a German operation code-named "China Blue, " which has British intelligence baffled. Based on real events that culminated in the Japanese attempt to invade India in 1944, The Fox in the Field is a vivid espionage thriller brimming with action, passion, and intrigue.
Keywords: World War (1939-1945) -- India